The role and importance of sanatoriums and boarding houses in restoring the workforce - Isroilova Dildoraxon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes fatigue and stress experienced by employees and workers in enterprises and organizations under the influence of various factors, as well as the role and importance of sanatoriums and boarding houses in relieving stress and restoring well-being. The study also examines modern management requirements in contemporary sanatorium-boarding facilities. Based on the research findings, a management model for sanatorium-boarding institutions has been developed, along with proposals for their further improvement.